An Integration Of Taguchi Method And Grey Relational Analysis In Optimizing Injection Moulding Processing Parameter Of Recycled Plastic - Zakarria, Noor Syuhadah (2014)
In this research, the effect of blending compositions of recycled polyamide 66 with 33% glass fiber filled (PA66-GF) is investigated and evaluated based on the dimensional stability, mechanical and rheological properties. Dalam kajian ini, kesan pengadunan komposisi poliamida 66 yang mengandungi 33% gentian kaca yang dikitar semula, disiasat dan dinilai berdasarkan kestabilan dimensi, sifat mekanik dan reologi.